Gambling in Connecticut adolescents: Prevalence, socio-demographic characteristics, trauma exposure, suicidality, and other risk behaviors - Elina A. Stefanovics; Zu Wei Zhai; Marc N. Potenza (PLoS ONE, 2025)
Adolescent gambling is a public health concern and has been linked to suicidality, various risk behaviors, and poor health outcomes. However, there is a limited understanding of specific risk and protective factors that may influence gambling behavior in Connecticut adolescents, especially in changing gambling environments. This study examines relationships between adolescents reporting gambling in the past-year and a range of health risk behaviors including vaping, traumatic experiences, academic performance, and receipt of social support. Data from the 2019 Youth Risk Behavior Survey in Connecticut high school students stratified by gambling status were examined in bivariate and multivariate analyses. Among 1,807 adolescents, past-year gambling was reported by 453 individuals [25.4%; 95% confidence interval [CI] = 22.7–28.1%]. Gambling prevalence was higher among older males and lower in adolescents of Asian origin. Gambling was further associated with suicidality and risk behaviors including substance use, smoking [traditional tobacco and electronic vapor use], risky use of digital technologies, unsafe sex, and aggressive behaviors. Gambling was also associated with traumatic experiences, depression/dysphoria, poor academic performance, and less familial social support. The results provide an up-to-date estimate of the current prevalence and correlates of gambling among Connecticut adolescents. The results provide recent estimates of the prevalence and correlates of gambling among Connecticut adolescents. The findings highlight the need for further investigation of specific factors like social support that help with designing and implementing tailored interventions.